HUBUNGAN DERAJAT KELAINAN RADIOLOGIK DENGAN DERAJAT NYERI PADA PENDERITA OSTEOARTRITIS SENDI LUTUT DI RUMAH SAKIT UMUM DAERAH KOTA KENDARI - HN, Muh Rustam; Ali, Agussalim; Rahma, Iis Ainu; Alifariki, La Ode (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Osteoarthritic (OA) is a degenerative disease with slow progressive which has a characteristic pathological sign of joint deterioration as a result of biochemical, metabolic, physiological, and pathological changes. Pain is a complaint that is generally felt by people with osteoarthritis and has a different degree in each patient. The purpose of this study determine the correlation between radiological abnormalities staging and pain level with osteoartritic of knee joint of Rumah Sakit Umum Daerah Kota Kendari. This research is an observasional analytic study with cross-sectional approach. 37 sampels were acquired through total sampling. Data were analyzed using the Spearman correlation test (p value <0,05). Result of the univariat analysis show that most patients have moderat radiological abnormality that was 12 (32.43%) and most of patient have severe pain level that was19 (51.35%). Based on bivariat statistical test, a positive correlation was obtained between radiological abnormalities staging and pain level with osteoartritic of knee joint with p=0,000 and r=0,831. There was a significant correlation between radiological abnormalities staging and pain level with osteoartritic of knee joint of Rumah Sakit Umum Daerah Kota Kendari.